Rebecca's garden Basic Gardening 1 (New York NBC Enterprises, 2003)
Rebecca Kolls teaches viewers of all gardening skill levels everything that they need to know about growing herbs, and she details a variety of different uses for fresh herbs, from baking to hair treatments to aromatherapy. ~ Dana Rowader, All Movie Guide
DVD
1
Keywords: Educational videos; Gardening; DVD-Video disks -- 2003